Le journaliste et le griot. Les traces de l’oralite dans la presse écrite Africaine - Frère, Marie-Soleil (Afrika Focus, 1999)
This paper will show the similarities between the journalist’s role and narrative style and those of the griot, a key player the traditional exercise of power. The new private press appeared in French-speaking Africa as a part of the democratic process at the beginning of the 1990’s, in the context of politic liberalization (multipartism, institutional renewal) and in the flow of a new type of political speech that allows contradictions, critiques and debates. The journalist, that had mostly been the mouthpiece of the governments until then, has acquired a new role as a conter-power in a democratizing regime. Nevertheless, the journalist may in some ways be compared to the traditional griot. First, his new form of speech is very close to the oral style of the griot. The stylistic characteristics, the use of metaphors and images, the way the story is built are common to both "story-tellers". Secondly, they both criticize the "Big Men", express the people’s frustrations and use irony to desacralised those in power. Thirdly, they occupy an "in between " position in society because, at the same time, they belong to the social group they are speaking or writing for, while being looked at as a different "cast" practising the power of public speech. The papers concludes that the griot and the journalist can play a role that enforces the democratization process in the sense that they make people share common values but they can also weaken the process by oversimplifying or hiding social problems and by supporting stereotypes and illusions. KEY WORDS :African press, griot, oral tradition, politics